1985
DOI: 10.1093/nar/13.6.2153
|View full text |Cite
|
Sign up to set email alerts
|

Maternal inheritance of transcripts from threeDrosophila src-related genes

Abstract: SU1MHARYThe =r2&pbhUj genome contains three major sequenoes related to the v-.A gene. Previously published molecular studies have confirmed the structural homology between v-Ar and two of the Droskph1aa sequences. We have sequenced a portion of the third v-gUM-related DroaolhUA gene and found that it also shares structural homology with vertebrate and Drosowb±A =-family genes. RNA sequences from each of the = genes are present in pre-blastoderm embryos indicating that they are of maternal origin. As embryogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Furthermore, even in embryos that were homozygous mutant for one of these three genes, heterozygosity for the two remaining genes did not lead to additive or synergistic increases in commissure defects (Table 3). Because in other experiments, Abl and trio behaved genetically as fra effectors (see below), the inability of fra to dominantly enhance Abl or trio loss-of-commissure defects, and the lack of transheterozygous interactions between fra, Abl and trio, may be due to the presence of maternally-contributed Abl and trio in the embryo (Bennett and Hoffmann, 1992;Liebl et al, 2000;Wadsworth et al, 1985). Another possibility is that heterozygosity for fra simply does not reduce the effective dose enough to enhance Abl or trio loss-of-commissure phenotypes.…”
Section: Df(1)np5/y;triomentioning
confidence: 96%
“…Furthermore, even in embryos that were homozygous mutant for one of these three genes, heterozygosity for the two remaining genes did not lead to additive or synergistic increases in commissure defects (Table 3). Because in other experiments, Abl and trio behaved genetically as fra effectors (see below), the inability of fra to dominantly enhance Abl or trio loss-of-commissure defects, and the lack of transheterozygous interactions between fra, Abl and trio, may be due to the presence of maternally-contributed Abl and trio in the embryo (Bennett and Hoffmann, 1992;Liebl et al, 2000;Wadsworth et al, 1985). Another possibility is that heterozygosity for fra simply does not reduce the effective dose enough to enhance Abl or trio loss-of-commissure phenotypes.…”
Section: Df(1)np5/y;triomentioning
confidence: 96%
“…In Drosophila, there are two src homologs, src42 (Src42A -FlyBase) and src64, and one Tec family kinase encoded by tec29 (Btk29A -FlyBase) (Takahashi et al, 1996;Katzen et al, 1990;Vincent et al, 1989;Gregory et al, 1987;Wadsworth et al, 1985;Simon et al, 1985;Simon et al, 1983). There is evidence that these genes play a role in cytoskeletal regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Hybridization and DNA sequence analyses have revealed that two of these genes, designated Dsrc and Dash, appear to be homologous to the vertebrate oncogenes src and abl, respectively (10,23). Transcripts from these genes are maternally inherited and are present on polyribosomes in preblastoderm embryos, indicating that they encode gene products active during early embryonic development (13,28). In addition, transcripts from Dsrc and Dash have been shown to be most abundant in embryos and pupae and to be present in lower amounts in larval and adult stages, except in adult ovarian tissue (23,26,28).…”
mentioning
confidence: 99%
“…Transcripts from these genes are maternally inherited and are present on polyribosomes in preblastoderm embryos, indicating that they encode gene products active during early embryonic development (13,28). In addition, transcripts from Dsrc and Dash have been shown to be most abundant in embryos and pupae and to be present in lower amounts in larval and adult stages, except in adult ovarian tissue (23,26,28). This pattern of expression correlates well with the periods of maximal cell division during Drosophila development and suggests, by analogy with vertebrate src family genes, that these genes may play a role in the regulation of cell proliferation.…”
mentioning
confidence: 99%
See 1 more Smart Citation